Are shipwrecks a real hazard for the ecosystem in the Mediterranean Sea?. Issue 1 (15th November 2017) - Renzi, Monia; Romeo, Teresa; Guerranti, Cristiana; Perra, Guido; Canese, Simonepietro; Consoli, Pierpaolo; Focardi, Silvano E.; Berti, Claudio; Sprovieri, Mario; Gherardi, Serena; Salvagio, Daniela; Giaramita, Luigi; et al.
Abstract: The aim of the present study was to evaluate the hazard from shipwrecks on communities by a holistic approach taking into account different effects on biological communities. Multibeam and Remotely Operated Vehicles surveys recorded ecological assessment of fish and benthic species on three shipwrecks flooded during the Second World War on Maërl beds habitats in the strait of Sicily. Pollution levels of a wide range of chemicals of ecotoxicological concern were also measured in sediments and in fish species from different trophic levels. Statistical analysis evidenced significant differences among pollutant levels between both sediments and fish collected in shipwreck sites and controls. Concerning fish, significant effects due to the vessel's cargo type and flooding position are recorded. In spite of that, our results underline that shipwrecks are also a hotspots of biodiversity and a habitat for preservation strategies in marine ecosystems that need to be monitored. Graphical abstract: Highlights: Multibeam and ROV surveys recorded ecological assessment on three shipwrecks. Pollution levels of chemicals were also measured in sediments and in fish. Significant differences among pollutant levels in shipwreck sites and controls Significant effects due to cargo type and flooding position were recorded. Shipwrecks are hotspots of biodiversity and an habitat for preservation strategies.